THE EFFECT OF USING COMPUTER-ASSISTED READING WITH INQUIRY BASED LEARNING ON STUDENT READING COMPREHENSION - Zakiyuddin Zakiyuddin (Language-Edu, 2022)
This study aims to determine whether there is a difference between students who read using computer-assisted reading and those who do not. Students' reading ability may depend on what they do every day. There are some students who understand vocabulary better by listening than what is written. reading while listening may be another way to overcome students' reading comprehension, There are some students who will memorize vocabulary for a long time because the vocabulary is often found in several sentences, and Some students will also easily memorize a lot of vocabulary because of the use of online dictionaries. With this, the researcher used lexical-tutor where there are audio-assisted reading, concordance, and online dictionary. For the learning process, researchers use inquiry based learning which focuses on student activity. For data collection, the researcher gave a question sheet based on what had been studied previously. The teaching materials are taken from the corpus in the lexical-tutor application    Research subject are selected from the student's representative on the basis of the student's English language skills. In order to understand whether students have an impact on their reading understanding of second-grade students, researchers use one-on-one T-TT test samples, as well as independent sample tests, to see if students use survey-based computer-aided reading to understand scores that differ from non-users. Based on the results of this study, the results of the study were then analyzed with paired TT-Test specimens, resulting in a Sig(2-Tailed) value of 0.052 > 0.05, while the data analyzed by the independent specimen test resulted in 679 >0.05. It can be concluded that there is no effect and no difference between survey-based learning with computer-assisted reading and reading without computer-assisted reading. In terms of individual scores, the findings suggest little progress. The researchers' monitoring results showed that not all students enjoyed reading while listening to audio. It is my hope that through this study, future researchers will be able to examine the learning process and the techniques used. In addition, more researchers can also take advantage of this research in the form of offline classes.